Legal Reform in Business Dispute Resolution: A Study of Legal Pluralism in Indonesia, Vietnam, and Thailand - I Gede Agus Kurniawan; Putu Aras Samsithawrati; Ni Ketut Supasti Dharmawan; Fradhana Putra Disantara; Ruetaitip Chansrakaeo (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
Legal pluralism in the resolution of business disputes in Indonesia, Vietnam, and Thailand illustrates the intricate interplay between the particular and the general elements of the national laws, international laws, and other legal systems, which allow for flexibility in resolving disputes, but at the same time brings problems for legal integration and certainty for the business people. This study examines the role of legal pluralism in the resolution of business disputes in Indonesia, Vietnam, and Thailand. Legal pluralism creates an interaction between national law, international law, and other legal systems, providing flexibility in dispute resolution while also posing challenges to integration and legal certainty for business practitioners. The research approach employed is a legal study focusing on literature regarding legal pluralism and business dispute resolution systems. The analysis method used is normative-qualitative, utilizing legislative, conceptual, and comparative methods. The research findings show that legal pluralism in business dispute resolution in Indonesia, Vietnam, and Thailand offers flexibility but also creates legal uncertainty. In Indonesia, the coexistence of civil, Islamic, and customary law leads to overlapping jurisdictions. Vietnam's state-controlled legal system incorporates arbitration and mediation but struggles with enforcing international awards. Thailand balances civil law with Buddhist-influenced mediation, favoring informal resolution but facing enforcement challenges. While legal pluralism enhances accessibility to justice, its effectiveness depends on legal integration and enforcement mechanisms to ensure certainty and fairness in business disputes.